2014
DOI: 10.1037/spq0000048
|View full text |Cite
|
Sign up to set email alerts
|

The scare tactic: Do fear appeals predict motivation and exam scores?

Abstract: Prior to high-stakes exams, teachers use persuasive messages that highlight to students the possible consequences of failure. Such messages are known as fear appeals. This study examined whether fear appeals relate to self-and non-self-determined motivation and academic performance. Data were collected in 3 waves. Self-report data pertaining to perceived fear appeals were collected in the first wave, self-report data pertaining to self-determined motivation were collected in the second wave, and exam scores we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 47 publications
7
58
0
3
Order By: Relevance
“…A disregarding appraisal resulted from low value of mathematics combined with a low expectation of success. These findings are in line with previous empirical work in this (Putwain and Remedios, 2014b;Putwain, et al, , 2015 and related areas (e.g., Preiss et al 2006;Putwain and Symes, 2012;Pekrun et al, 2004Pekrun et al, , 2011). …”
Section: Discussionsupporting
confidence: 83%
“…A disregarding appraisal resulted from low value of mathematics combined with a low expectation of success. These findings are in line with previous empirical work in this (Putwain and Remedios, 2014b;Putwain, et al, , 2015 and related areas (e.g., Preiss et al 2006;Putwain and Symes, 2012;Pekrun et al, 2004Pekrun et al, , 2011). …”
Section: Discussionsupporting
confidence: 83%
“…When appraised as threatening, fear appeals result in higher test anxiety, a higher performance-avoidance goal (to avoid performing worse than one's classmates), lower intrinsic motivation, and lower grades on tests and examinations (Putwain & Best, 2011, 2012Putwain & Roberts, 2009;Putwain & Remedios, 2014b;Putwain & Symes, 2011a,2011bSprinkle, Hunt, Simonds, & Comadena, 2006). These findings are broadly consistent with those from adjacent areas of the educational psychology literature.…”
Section: Fear Appeals In the Classroomsupporting
confidence: 80%
“…On the basis of this one would expect that challenge and threat appraisal of fear appeals would also be likely to influence subsequent educational achievement. Previous research has shown how the threat appraisal of a fear appeal is related to lower achievement (Putwain & Remedios, 2014b;Putwain & Symes, 2011b) however research has yet to empirically demonstrate how challenge appraisals relate to subsequent educational achievement. The higher academic self-efficacy and attainment value resulting from a challenge appraisal would strongly suggest that higher achievement would be the likely outcome.…”
Section: Fear Appeals Appraisals and Educational Achievementmentioning
confidence: 99%
“…Judgments concerning one's resources and options for responding to the demands presented in the fear appeal have been established through academic self-efficacy, the belief that one can learn or perform a particular task (Bandura, 1997;Schunk & Pajares, 2002), and expectancy of success, the belief that one is capable of effecting a successful outcome on a particular task Wigfield & Eccles, 2000;Wigfield et al, 2009). Studies have shown that challenge appraisal follows from high attainment/ utility value and high academic self-efficacy/ expectancy of success whereas threat appraisal follows from high attainment/ utility value with low academic self-efficacy/ expectancy of success (Putwain & Remedios, 2014b;Putwain, Remedios, & Symes, 2014). …”
Section: The Appraisal Of Messages Used By Teachers Prior To High-stamentioning
confidence: 99%